Gastric mucosa alterations after different post-gastrectomy assemblies.: comparative study in dogs - Fernández Naone, Gonzalo; Guariglia, Roque; Abelleira, Alfredo; Cordillo, Felipe; Palacios, Gerardo; Olazábal, Mario; Bonaba, Roberto (Cirugía del Uruguay, 1987)
The authors study changes in gastric mucosa after different post-gastrectomy assembiles, employing three series of seven, eight, and five animals each. Chronic gastritis of various degrees and intestinal metaplasia ranging from minimal to moderate was ·obtained. The authors come to the conclusion that le• sions are most severe after gastrojejunostomy, inter• mediate after gastrojejunostomy on Roux-en-Y loop, and milder after gastroduodenostomy.